Chapter «Il segreto e la sua custodia sono un elemento fondamentale del potere». Non luogo a procedere - Pellegrini, Ernestina (Biblioteca di Studi di Filologia Moderna, 2021)
The contribution reworks an essay published in the journal «LEA» (2015) through combining it with a short paper presented at a Conference (2019) introducing readings of excerpts from Magris' Non luogo a procedere. The essay also adds some critical considerations suggested by more recent studies published at an international level close to the translations and corresponds to the conclusion of the second Meridiano of Mondadori devoted to the writer's works. It takes on a sum of knowledge that transformed it, gradually assuming a somewhat exorbitant dimension. A work represents for Magris the sea into which all the rivers of writing have flowed, just as for Pirandello with his Uno, nessuno e centomila.